Criopreservação de sêmen de tambaqui Colossoma macropomum em macropalhetas Sergipe - Dias Filho, Vinicius Augusto (2015)
Cryopreservation of fish semen is a key to optimization of reproductive management, the formation of germplasm bank and the development of genetic improvement programs. The success of this technique depends on the management and balance of several factors such as the collection, dilution, packaging, freezing and thawing. Tambaqui semen cryopreservation protocols have been developed using 0.5 mL straws on packaging. However, the high volumes of semen produced and the elevated taxes of fecundity are presented by this specie, it is necessary to use larger volume storage containers for application to large-scale production. The objective of this study was to establish a tambaqui semen cryopreservation protocol in large straw 4,0mL, from the definition of cryosolution, equilibration time and the best ratio between temperature and time semen thawing. The semen collected was diluted, packaged in large straws, frozen in liquid nitrogen which was conditioned in dry-shipper and stored in cryogenic cylinder at -196 °C. In the first experiment, different cryosolutions (M1 - 5% 5% methylglycol; M2 - 5% 5% methylglycol+ 5% egg yolk; M3 - 10% 5% methylglycol; M4 - 10% 5% methylglycol + 5% egg yolk; M5 - 15% 5% methylglycol; M6 - 15% de 5% methylglycol + 5% egg yolk) and three equilibration times (4, 20 and 40 minutes) were tested. In the second experiment, different relation between temperature and time thawing on sperm quality (30ºC for 50s - T1; 30ºC for 80s - T2; 60ºC for 25s - T3 e 60ºC for 40s - T4) were evaluated. In conclusion, this study showed that the ideal protocol for cryopreservation of tambaqui semen in large straw 4,0mL is made by diluting semen at a ratio of 1: 9 (v: v) in a medium composed of 5% methylglycol and 5% egg yolk. Both of them must have remained in contact with each other for 4 minutes until both were subjected to freezing in dry-shipper. The thawing of samples required to be performed in a water bath at 60 ° C for 25s.